3D Geospatial Analysis of Soil Unit Weight Using the Radial Basis Function (RBF) and Ordinary Kriging (OK) Methods in Ketahun Sub-district, North Bengkulu - Nafisa Auliya; Lindung Zalbuin Mase; Khairul Amri; Rahmat Fahrizal; Rena Misliniyati; Hardiansyah - (Lambung Mangkurat University Press, 2026)
Ketahun is one of the areas in North Bengkulu Regency, Bengkulu Province, which is affected by seismic activity, with geological conditions dominated by sedimentary from Bintunan Formation, which influence soil characteristics for geotechnical planning. Previous research on three-dimensional (3D) geospatial modeling in Bengkulu region was generally limited to soil technical parameters, while soil unit weight parameters were rarely used. This study aims to make 3D modeling of subsurface structure and soil unit weight distribution (γsat, γb, and γd) in Ketahun using geospatial approach. The research utilize data from field investigations at 15 Cone Penetration Test (CPT) points, which were then empirically correlated determine soil unit weight values. The 3D modeling was built using Leapfrog Geo application, through the Implicit Geological Modeling approach based on Radial Basis Function (RBF), while the distribution of bulk density parameters was estimated using Ordinary Kriging (OK). The validation results showed an R2 (0,95 - 0,96), RMSE (0,48 – 0,55), and MAE (0,34 – 0,46) proving that this 3D model is able to represent the spatial distribution of soil parameters measurably, with consistence parameter relationships, where γsat > γb > γd. The average values obtained for untuk γsat is 19,77 kN/m3, γb is 19,67 kN/m3, and γd is 15,82 kN/m3. The results of this study are expected to provide insight into the subsurface and distribution of bulk density to further geotechnical analysis for support the planning of earthquake-resistant building structures.